An XML knowledge base system for scheduling problems - Varela, M.L.R. (2002)
Production Scheduling is an important function strongly contributing to the competitiveness of industrial and service companies. In this communication we make a contribution for XML based specification of scheduling concepts in order to allow for a standard representation of scheduling problems and related tasks. This information modeling is used in the development of a web based decision support system for the resolution of scheduling problems. An XML-based Knowledge Base System may be useful not only to facilitate the specification of scheduling problems but also in the search for the most suitable available algorithms and methods, which can then be used for finding good solutions to the problems. The existing algorithms, as well as their corresponding implementations, may either be local or remotely available, through the Internet.